Variability of lower limb artery systolic–diastolic velocities in futsal athletes and non-athletes: evaluation by arterial doppler ultrasound - Duarte-Mendes, Pedro (2020)
Background: Sports athletes, namely high-intensity practitioners, suffer from vascular remodeling overtime. The purpose of this study was to analyze the systolic and diastolic velocities' variation between non-athletes and futsal athletes by means of arterial lower limb doppler ultrasound. Additionally, we intended to verify if the velocity variations occur primarily at the systolic or the diastolic level and in which arteries. Methods: Seventy-six young males (mean ± SD: 24.9 ± 2.8 years old) volunteered to participate in this cross-sectional study and were divided into two groups: a futsal athletes group (n = 38; 24 ± 2.78 years) in the central region of Portugal playing on the 2nd national league with the same level of practice (16 ± 2.4 years of practice) and a non-athletes group (n = 38: 26 ± 1.8 years) who did not practice sports regularly and were not federated in any sport. All the subjects agreed to participate in the study with the aim of assessing the arterial lower limb through doppler ultrasound (Philips HD7 echograph with linear transducer 7-12 MHz). Results: Differences between groups (p ≤ 0.05) in the systolic velocity of the left deep femoral artery (p = 0.022; d = 0.546, small) and in the right superficial femoral artery (p = 0.028; d = -0.515, small) were found. We also found differences in the diastolic velocity: in the left common femoral artery (p = 0.002; d = -0.748, moderate), in the right deep femoral artery (p = 0.028; d = -0.521, small), in the right superficial femoral artery (p = 0.026; d = -0.522, small), in the right popliteal artery (p = 0.002; d = -0.763, moderate), and in the left popliteal artery (p = 0.007; d = -0.655, moderate). Moreover, the athletes' group presented the highest mean values, with the exception of the systolic velocity of the left deep femoral artery. In intragroup analysis of variance referring to systolic and diastolic velocities in arterial levels in the right and left arteries, differences were found in all analyses (p ≤ 0.05). Conclusions: We conclude that futsal athletes of our sample go through a process of changes such as increased blood flow velocity in systolic and diastolic cardiac phase in all studied lower limb arteries, showing that the remodeling occurs regardless of vessel radius. Our results reinforce the existence of vascular remodeling that may vary with the sport and its intensity.